Mawlana Mawdudi and political Islam : authority and the Islamic state - Jackson, Roy, 1962- (Routledge, 2011)
Mawlana Mawdudi was one of the most influential and important Islamic thinkers of the modern world, whose brand of political Islam has won widespread acceptance in South and South East Asia as well as the Middle East. He was not only an Islamic scholar, but also a journalist and political activist who founded the Jama'at-i-Islami, which has subsequently influenced the development of many Islamic movements and parties throughout the Muslim world. This book is the first to critically engage and assess his career and legacy within the wider context of political Islam. It includes coverage of his.